Peran Guru dalam Penanaman Budi Pekerti pada Anak Usia Dini di RA Syihabuddin Klandungan Dau Malang - Lailatul Mukarromah; Anwar Sa’dullah; Yorita Febry Lismanda (Jurnal Dewantara, 2020)
This study aims to describe the role of teachers in the cultivation of character in early childhood, to describe the cultivation of character in children, and to identify supporting and inhibiting factors in the cultivation of character in early childhood in RA Syihabuddin Klandungan Dau Malang. The method used by researchers is to use qualitative research. The instrument used by researchers was the presence of researchers, observation sheets, recording equipment, and stationery. The research location is Tirtomulyo Street No. 66C Klandungan Dau Malang. The conclusions in this study are (1) The role of teachers in the cultivation of manners in early childhood in RA Syihabuddin Klandungan Dau Malang, namely teachers as instructors, mentors, role models, facilitators, leaders, motivators, evaluators, teachers must be good instructors in teaching children her students. (2) Shaking hands by kissing the hand of the teacher, being polite to the teacher, speaking politely towards the teacher, being obedient to the teacher, fostering harmony, discipline, being generous, being brave, being patient when waiting in line, learning to respect and respect others, eating and drinking, praying before and After Eating or Before and After Activity. (3) teachers who are committed in implementing the cultivation of manners. While the inhibiting factors in the cultivation of manners in early childhood in RA Syihabuddin Klandungan Dau Malang include a small proportion of parents who hand over their children's education to schools and the inconsistency of some parents in habituating children to behave well.